Thermostability and polymorphism of theobroma oil and palm kernel oil as suppository bases - Noordin, M.I.; Chung, L.Y. (2009)
Thermal stability of pharmaceutical ingredients is an important aspect. In this study, we adopted differential scanning calorimetry (DSC) to investigate thermal stability of suppository bases, theobroma oil (cocoa butter) and a palm kernel oil (PKO) blend. The study shows theobroma oil possesses six polymorphic forms whilst the palm kernel oil blend has three. Upon rescanning, the PKO blend does not show changes in the enthalpy of fusion and the melting point with time, whilst the theobroma oil shows significant reduction, and only regained its thermal stable state after 10 days. This indicates that PKO blend possesses better thermal stability.